Pregnant Women and Malaria Preventive Measures: A Case of Tamale Teaching Hospital, Ghana - Abdul Rauf Alhassan (Journal of Tropical Medicine)
Background. In Saharan Africa, an estimated 25 million pregnancies are all at risk of malaria every year, with substantial morbidity and death effects for both the mother and the fetus. Aim. To investigate the use of malaria preventive measures among pregnant women patronizing antenatal services of Tamale Teaching Hospital. Methodology. This study was conducted using a descriptive cross-sectional survey of 250 participants. Data analysis was done with SPSS version 20. Graphs and tables were used to present the study data. Bivariate analysis was done using Chi-square use to determine the relationships and binary logistics regression used for identification of predictor variables. Results. The mean age of the study participants was 30.0 ± 4.5 years and most of them (73.0%) were within the age group of 25–35 years. Respondents’ favorable knowledge, a favorable attitude, and favorable practice were 78.0%, 62.0%, and 57.6%, respectively. And the following variables were associated with malaria preventive practice: age of the respondent (X2 = 6.276, P=0.043), religion (X2 = 6.904, P=0.032), level of education (X2 = 41.482, P<0.001), employment status (X2 = 20.533, P<0.001), monthly income (X2 = 21.838, P<0.001), and attitude level towards malaria prevention (X2 = 35.885, P<0.001). Further analysis revealed educational level and attitude level as predictors of malaria preventive practice. Conclusion. This study recorded favorable knowledge, attitude, and practice with regards to malaria prevention among more than half of the study participants.